Assessment of Preferred Method of Temporisation Technique in Single Crown Tooth Preparation - A Retrospective Study - R, KEERTHIKA; HARIPRIYA, S; SUGUMARAN, SURENDAR (The journal of contemporary issues in business and government, 2021)
Temporary restoration are used for short or long term between the time of tooth preparation until the definitive indirect restorations are fitted.Various techniques are used to fabricated these restorations- direct ,indirect ,combination of both.The aim of this study was to assess the preferred method of temporisation in single teeth crown preparation.This study was conducted at a private dental institute between June 2019 to March 2020. 86000 patient records were analyzedTotal of 976 teeth which had temporary crowns following single tooth crown preparation were included and assessed for technique of fabrication with gender of the patient,type of teeth temporised and the technique used for temporisation.The tabulated data was analysed using SPSS software .Incomplete date were excluded from the study.Statistical analysis was done using a chi -square test.In our study we observed that maximum number of temporisation procedures was done in males with predominance in maxillary posteriors.Association between the type of teeth restored and the temporisation technique showed that direct technique was the most preferred technique and it was most commonly done in maxillary posteriors (p <0.05).The interim restoration plays a significant role in maintaining the occlusal function and protects the prepared tooth, hence proper temporisation is required following tooth preparation.